PERAN MEDIA GAMBAR DALAM MEMBANGUN KERUNTUTAN ALUR BERCERITA SISWA KELAS RENDAH SD - Iya Anggraeni; Sahrul Gunawan, Asep (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Storytelling ability is one of the essential competencies in Indonesian language learning at the elementary school level, particularly for lower-grade students (grades I, II, and III). Lower-grade students often face difficulties constructing coherent and sequential story plots due to their cognitive development, which remains at the concrete operational stage. Picture media emerges as a pedagogical solution that can facilitate students' visual thinking processes in building narrative coherence. This study aims to analyze the role of picture media in building the coherence of storytelling plots for lower-grade elementary school students through a systematic literature review of 12 relevant research articles published between 2020 and 2024 with full access. The findings reveal that various types of picture media—sequential pictures, illustrated series, picture illustrations, and literacy-based picture media—have consistently proven to help lower-grade students organize their story plots in a sequential and chronological manner. Picture media functions as visual scaffolding that provides concrete thinking frameworks, stimulates imagination, and encourages the use of clear narrative structures. The implication of these findings is the importance of integrating structured picture media in Indonesian language learning for lower-grade elementary school classrooms.